Education, underemployment, and job satisfaction - Shujaat Farooq; Usman Ahmed; Rehmat Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2008)
Education is an effective vehicle for producing the required skills to maintain economic growth. The benefits of education range from human to economic, social and cultural. In Pakistan, there is significant rise in the average level of education, but over time, more and more workers incapable to use their educational background on the job. Supply of labor may have outstripped the demand of labor in some professions, and high qualified peoples taking job on low positions. Such underemployment/overeducation has not been fully explored in Pakistan. The theme of paper is "underemployment symbolizes an inefficient usage of human resources and lost output for society". The research is based on case study on clerical workers of SNGPL. By comparing their educational backgrounds with their nature of job, this paper examines the impact of overeducation on job satisfaction. Our results show that underemployment/overeducation is correlated with higher level of job dissatisfaction, reduced job involvement, impaired co-worker relationship, and more emphasis on future aspirations.
Keywords: 330; Sui Northern Gas Pipeline Limited (SNGPL); Job satisfaction; Underemployment; overeducated clerical workers